A review of the status and decline in abundance of the Irish Hare (Lepus timidus hibernicus) in Northern Ireland - Dingerkus, Karina; Montgomery, Ian (2002)
The Northern Ireland Hare Survey documented the distribution of the Irish Hare (Lepus timidus hibernicus). Historical game bag records and other, more contemporary, records of hare distribution were examined. These data indicate how numbers of L t. hibernicus may have changed over the last 140 years. The results of the Northern Ireland Hare Survey suggested that L. t. hibernicus was widespread throughout Northern Ireland. Current average densities are no more than 0.65 hares/km(2). Game bag records indicate that hare densities may have been much higher in the past, with a maximum of 138 hares/km(2) recorded on Crom Estate, Co. Fermanagh, in 1864. Evidence from hare distribution recorded during the Northern Ireland Rabbit Survey indicates that hare numbers declined between 1984 and 1994. Evidence from all sources suggests that L. t. hibernicus has declined in abundance substantially, with present total population estimates for Northern Ireland ranging from 8250 to 21000 individuals. Flushing data indicate that rushes and hedgerows are important diurnal resting areas for hares. While the principal reason for the decline in numbers of L. t. hibernicus in Northern Ireland is not clear, more species-rich pasture and provision of areas of cover, such as rushes, may arrest further declines, or indeed promote numbers of hares, particularly in lowland areas.